Special Paper 438: Ophiolites, Arcs, and Batholiths: A Tribute to Cliff Hopson 2008
DOI: 10.1130/2008.2438(03)
|View full text |Cite
|
Sign up to set email alerts
|

Tonalites, trondhjemites, and diorites of the Elder Creek ophiolite, California: Low-pressure slab melting and reaction with the mantle wedge

Abstract: The Elder Creek ophiolite, which crops out along the South, Middle, and North Forks of Elder Creek, is the largest exposure of mid-Jurassic Coast Range ophiolite in the northern Coast Ranges of California. The Elder Creek ophiolite contains almost all of the components of a classic ophiolite (mantle tectonites, cumulate ultramafi cs and gabbro, dike complex, volcanics), although most of the volcanic section has been removed by erosion and redeposited in the overlying Crowfoot Point breccia. It differs from cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…1; Hopson et al, 1981Hopson et al, , 2008Shervais and Kimbrough, 1985). This ophiolite consists largely of crustal rocks, including both plutonic rocks (i.e., gabbros and diorites) and volcanic or hypabyssal rocks (i.e., boninites, basalts, basaltic andesites, and dacites) (Giaramita et al, 1998;Shervais et al, 2004Shervais et al, , 2005aHopson et al, 2008;Shervais, 2008). It has been dated to between 165 and 172 Ma using U-Pb zircon (Kimbrough in Shervais et al, 2005a;Hopson et al, 2008;Mattinson and Hopson, 2008) and 39 Ar-40 Ar on basaltic glass (Shervais et al, 2005a), and as middle to early late Jurassic (Bajocian through Kimmeridgian) using radiolarian assemblages (Murchey in Shervais et al, 2005a).…”
Section: Regional Settingmentioning
confidence: 97%
“…1; Hopson et al, 1981Hopson et al, , 2008Shervais and Kimbrough, 1985). This ophiolite consists largely of crustal rocks, including both plutonic rocks (i.e., gabbros and diorites) and volcanic or hypabyssal rocks (i.e., boninites, basalts, basaltic andesites, and dacites) (Giaramita et al, 1998;Shervais et al, 2004Shervais et al, , 2005aHopson et al, 2008;Shervais, 2008). It has been dated to between 165 and 172 Ma using U-Pb zircon (Kimbrough in Shervais et al, 2005a;Hopson et al, 2008;Mattinson and Hopson, 2008) and 39 Ar-40 Ar on basaltic glass (Shervais et al, 2005a), and as middle to early late Jurassic (Bajocian through Kimmeridgian) using radiolarian assemblages (Murchey in Shervais et al, 2005a).…”
Section: Regional Settingmentioning
confidence: 97%
“…The most common suites are similar to those found in the Coast Range ophiolite: (1) a primary suite of cumulate dunite and layered gabbros composed of plagioclase and clinopyroxene, with less common olivine, orthopyroxene, or hornblende; (2) a later intrusive suite of wehrlites, pyroxenites, and primitive isotropic gabbros; and (3) a fi nal suite of calc-alkaline dikes and plutons composed of tonalitetrondhjemite-quartz diorite, which may grade into isotropic gabbro as modal quartz declines (Shervais, 2001(Shervais, , 2008Shervais et al, 2004).…”
Section: Plutonic Rock Parent Magmasmentioning
confidence: 82%
“…Nonetheless, its origin is controversial and three primary hypotheses have been advanced: (1) formation at a mid-ocean-ridge spreading center at low paleolatitudes, and subsequent rapid drift northward to collide with North America (Hopson et al, 1981Pessagno et al, 2000); (2) formation as a backarc basin behind an east-facing volcanic arc that collided with North America during the Late Jurassic Nevadan orogeny (Godfrey and Klemperer, 1998;Ingersoll, 2000); and (3) formation by forearc or intra-arc rifting along the western margin of North America, in response to nascent or renewed subduction of oceanic plates beneath North America (Shervais and Kimbrough, 1985;Shervais, 1990Shervais, , 2001Stern and Bloomer, 1992). The consensus of most recent studies support the suprasubduction-zone model (Stern and Bloomer, 1992;Shervais et al, 2004Shervais et al, , 2005aShervais, 2008 Subduction initiation along transform faults: The proto-Franciscan subduction zone | RESEARCH Choi et al, 2008a;Jean et al, 2010), but models based on backarc basins and oceanic spreading centers still persist (e.g., Hopson et al, 2008).…”
Section: Coast Range Ophiolitementioning
confidence: 92%
See 1 more Smart Citation
“…Wenge et al (2005) experimentally showed that tonalitic and granodioritic melts can be formed by solid dehydration melting of amphibolite at 2.0 GPa and 850-1000 °C. On the other hand, tonalitic arc magmatism was reported from oceanic subduction zone settings (Giunta et al, 2006;Shervais, 2008). Yan et al (2010) also suggested 2 possible sources for the origin of tonalitic magma in the granitic rocks from the Nansha microblock (South China Sea): i) partial melting of Precambrian continental basement and Precambrian rocks, and ii) mantle-derived magma, which results from the interaction of released fluids from subducted slab and the overlying mantle wedge.…”
Section: Discussionmentioning
confidence: 99%